The Influence of Human Resource Management Practices on Service Organization Performance Public Through Involvement and Development Competence of Government Employees Southeast Sulawesi Province - ., Kafarudin; Kamaludin, Murdjani; ., Juharsah; Masri, Muhammad (International Journal of Membrane Science and Technology, 2023)
This research aims to determine the influence of human resource management practices on the service performance of public organizations through the involvement and development of competency of employees within the Southeast Sulawesi Provincial Government.Human resource management is the process of acquiring, training, assessing, providing compensation, paying attention to work relationships, health, security and justice issues (Dressler, 2015:2). Human resource management is specifically required to focus on all activities related to humans (Ivancevich, 2014:34). Human resource management is related to the organization’s formal planning system to determine the effectiveness and efficiency of employee talents to realize organizational goals (Malthis and Jackson, 2011: 14). Human resource management in an organization is a key factor in organizational continuity and future development.The location of this research is the Southeast Sulawesi Provincial Government. This research uses a combination of descriptive statistical analysis and inferential statistical analysis to analyze the data. The population of interest for this research is all Regional Apparatus Organizations (RAO) within the scope of the Southeast Sulawesi Provincial Government, consisting of a total of 50 RAO. The sample in this study consisted of 100 employees who held high-level leadership and administrative positions responsible for human resource development in the Regional Government Organization of Southeast Sulawesi Province.This study found that good and appropriate human resource management practices contribute significantly to increasing employee participation, involvement and cooperation in the organization. However, this research also found that human resource management practices alone cannot directly improve employee competency development. Practices such as increasing skills, motivation and opportunities were found to be ineffective in increasing employee competency development.The lack of direct impact on competency development results in the inability of competency development to mediate the influence of human resource management practices on improving organizational performance in public services within the Southeast Sulawesi Provincial Government. Therefore, the study concludes that while human resource management practices play an important role in increasing employee participation and cooperation, they do not directly contribute to improving employee competency development and organizational performance in the public service sector.The findings of this research have an impact on organizations in the public service sector, especially within the Southeast Sulawesi Provincial Government, in terms of human resource management practices and employee competency development. This study also emphasizes the importance of considering the mediating role of employee competencies in the relationship between human resource management practices and organizational performance. Future research could explore other potential mediators or moderators to gain a deeper understanding of this relationship. Overall, the findings suggest that a comprehensive approach to human resource management, including competency development practices and initiatives, is critical to improving organizational performance in the public service sector.This study contributes to the existing literature by examining the relationship between human resource management practices, employee competency development, and organizational performance in the public service sector. It adds to knowledge with a special focus on the Provincial Government of Southeast Sulawesi, providing insight into the unique context of this region. This research uses a combination of quantitative and qualitative research methods, including document analysis and Likert scale measurements, to collect data and analyze the relationships between variables. It acknowledges and builds on previous relevant studies, such as those by Tensay and Singh (2020), Sivapragasam and Raya (2017), Rich et al. (2010), Kehoe and Wright (2013), Sun et al. (2007), and Kuvaas (2008), to provide a comprehensive understanding of the topic.